2021
DOI: 10.55562/jrucs.v44i1.139
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Neonatal Jaundice at Al Kadhimiya Pediatrics Hospital in Baghdad, Iraq

Taha Sadeq,
Hamid Feyad,
Ghassan Abdul Hameed

Abstract: Jaundice is the most common condition that requires medical attention in newborns. Jaundice is observed during the 1st wk after birth in approximately 60% of term infants and 80% of preterm infants. Early identification of neonates at great risk of Neonatal Hyperbilirubinemia is of paramount importance in preventing brain damage.Objectives: to investigate the prevalence and risk factors associated with neonatal jaundice at Al Kadhimiya pediatrics hospital.Materials and Methods: A cross sectional study was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
0
1
Order By: Relevance
“…In terms of mothers' delivery modes, the greatest percentage (71.6%) were delivered by cesarean section and only 28.4% were delivered by normal vaginal delivery, the results do not support with study findings of a descriptive study to evaluate Kurdish mothers' practices regarding newborn jaundice management which found that (69%) of mothers delivered by normal vaginal NVD and only (31%) delivered by Caesarean section CS (19) . Also, in disagreement with our study, a study from Iraq had shown that the percentage of normal vaginal delivery (NVD) was (58.1%) and (41.9%) for cesarean section (20) .…”
Section: Discussioncontrasting
confidence: 99%
“…In terms of mothers' delivery modes, the greatest percentage (71.6%) were delivered by cesarean section and only 28.4% were delivered by normal vaginal delivery, the results do not support with study findings of a descriptive study to evaluate Kurdish mothers' practices regarding newborn jaundice management which found that (69%) of mothers delivered by normal vaginal NVD and only (31%) delivered by Caesarean section CS (19) . Also, in disagreement with our study, a study from Iraq had shown that the percentage of normal vaginal delivery (NVD) was (58.1%) and (41.9%) for cesarean section (20) .…”
Section: Discussioncontrasting
confidence: 99%